Pengoptimalan Strategi Pemasaran Produk UMKM Melalui Platform Online Shop pada Komunitas Kreatif Ibu-ibu di Kecamatan Wonotunggal - Fauzi, M. Fauzi; Zurohman, Achmad (Welfare : Jurnal Pengabdian Masyarakat, 2023)
In the current digital era, there are still many MSMEs who have difficulty marketing their products effectively in online shops. This training program aims to help increase sales of MSME products in the community of creative mothers in Wonotunggal District. The implementation method used is mentoring, consisting of workshops, training materials, online discussions, marketing competitions, and direct practice. The result of implementing this activity is that mentoring has had an impact on the community of creative mothers in Wonotunggal District in the form of increasing sales, increasing brand awareness, strengthening skills, improving product quality, and strengthening relationships in the community. This. In this training, the role of companions is very important in providing support, guidance, and motivation for community members.